An Alternative Natural Deduction for the Intuitionistic Propositional Logic - Ilić, Mirjana (Bulletin of the Section of Logic, 2016)
A natural deduction system NI, for the full propositional intuitionistic logic, is proposed. The operational rules of NI are obtained by the translation from Gentzen’s calculus LJ and the normalization is proved, via translations from sequent calculus derivations to natural deduction derivations and back.